Estimation of ischemic core in acute ischemic stroke with CT angiography and non-contrast CT: Attenuation changes in ASPECTS regions vs. automated ASPECTS scoring - Li, Jing; Peng, Yuling; Liu, Jiayang; Wu, Jiajing; Yao, Yunzhuo; Gu, Sirun; Zhang, Zhiwei; Li, Yi; Wang, Jingjie; Li, Yongmei (Frontiers in Neuroscience, 2022)
Purpose Reperfusion therapies for acute ischemic stroke due to large-vessel occlusion (AIS-LVO) are highly time-dependent and large infarction is related to poor outcome and risk of symptomatic hemorrhage. It is of significance to investigate and optimize the screening means and selection criteria for reperfusion therapies to identify more appropriate patients with better outcomes. This study aimed to compare the performance of attenuation changes versus automated ASPECTS and using CTA source images versus NCCT in distinguishing the infarction extent of ischemic core volumes ≥ 70 mL within different time windows. Methods Seventy-three patients with AIS-LVO who received multimodal CT were analyzed. Automated software was used to calculate ASPECTS. Attenuation change was defined as the sum of products of relative Hounsfield Unit (rHU) values times weighting factors of all 10 ASPECTS regions. rHU value of each region was the HU of the ischemic side over that of the contralateral. The corresponding weighting factors were the regression coefficients derived from a multivariable linear regression model which was used to correlate regional rHU with ischemic core volumes, because each region in the ASPECTS template is weighted disproportionally in the ASPECTS system. Automated ASPECTS and attenuation changes were both calculated using CTA and NCCT respectively. Results Attenuation changes were correlated with ischemic core volumes within different time windows (Rho ranging from 0.439 to 0.637). In classification of the ischemic core ≥ 70 mL, the performances of attenuation changes were comparable to ASPECTS (AUC ranging from 0.799 to 0.891), with DeLong’s test (P = 0.079, P = 0.373); using CTA (AUC = 0.842) was not different from NCCT (AUC = 0.838). Conclusion Attenuation changes in ASPECTS regions were correlated with ischemic core volumes. In the classification of infarction volumes, attenuation changes had a high diagnostic ability comparable to automated ASPECTS. Measurement of attenuation changes is not involved in complicated scoring algorithms. This measurement can be used as an available, rapid, reliable and accurate means to evaluate infarction extent within different time windows. The usefulness of infarction volumes measured by attenuation changes to identify more appropriate patients for reperfusion therapies can be validated in future clinical trials.